Disclosure of cancer diagnosis to the patient: A cross-sectional assessment of public point-ofview in Saudi Arabia - Essmat A Mansour; Isabelita N Pandaan; Essmat M Gemeay; Ayat H Al-Zayd; Eman K Alenize (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Cancer is still the most difficult diagnosis that the physicians encountered and found themselves facing the issue of announcement and disclosure of a diagnosis for both families and patients. Aim: The aim of this study is to assess the attitudes of the public people toward the disclosure of cancer diagnosis to patients in Saudi Arabia. Material and methods: This study was cross-sectional study. The data were collected randomly using simple random sampling method from 510 participants from general population; one tool was used based on the previous studies. It contains two parts; the fi rst was the sociodemographic data of the participants and questions related to cancer information and attitude toward disclosure of cancer diagnosis. Results: Majority of participants preferred to inform the patients with a rational to help in treatment, also signifi cant correlations were found between the demographic characteristics and various responses of the cancer information. Conclusion: Majority of participants prefer to inform the patients about cancer diagnosis to help in treatment and prepare their life.